Compensation Preferences: The Role of Personality and Values - Julian, Amanda M.; Wijngaard, Onno; de Vries, Reinout E. (Frontiers in Psychology, 2021)
The present study investigated relations between personality and values on the one hand and compensation preferences on the other. We hypothesized that HEXACO Honesty-Humility and self-transcendence versus self-enhancement values predict preference for higher relative compensation level and that HEXACO Openness to Experience and openness to change versus conservation values predict preference for compensation variability. Furthermore, we expected perceived utility of money and risk aversion to mediate the respective relations. The hypotheses were tested using a sample of 2,210 employees from a large international organization. The results provided support for the direct and mediated relations between personality and values on the one hand and preferences for compensation variability and level on the other.